Molecular Mechanisms of Ligusticum Wallichii and Its Components in Attenuating Acute Cerebral Vasospasm - Bo-Wen Wu; Pei-Yu Yan; Mi-Shan Wu (World Journal of Traditional Chinese Medicine)
Objective: Acute cerebral vasospasm (aCVS) is a severe complication commonly occurring after subarachnoid hemorrhage, leading to significant morbidity and mortality despite current therapeutic interventions. This study aims to elucidate the potential therapeutic mechanisms of Ligusticum wallichii (L. wallichii) against aCVS through an integrated approach of bioinformatics, meta-analysis, and network pharmacology. Materials and Methods: Studies related to L. wallichii and aCVS were systematically retrieved from public databases, followed by a meta-analysis on the effectiveness of L. wallichii extracts in treating or preventing aCVS. Major components were identified through the Traditional Chinese Medicine (TCM) Systems Pharmacology database, with their three-dimensional structures obtained from PubChem. Target predictions on human proteins were performed using PharmMapper, and these were complemented by ribonucleic acid sequencing differentially expressed genes (DEGs) analysis of the dataset GSE37924. An intersection analysis was performed to explore the overlap between predicted targets. Protein–protein interaction, Gene Ontology, and Kyoto Encyclopedia of Genes and Genomes enrichment analyses were conducted, followed by the construction of a pharmacological network using Cytoscape. The key components and their predicted targets were further analyzed and validated through molecular docking simulations. Results: The meta-analysis revealed that tetramethylpyrazine, a key component of L. wallichii extracts, showed significant potential in alleviating and preventing symptoms of aCVS. Key components, such as beta-sitosterol, folic acid, mandenol, myricanone, perlolyrine, senkyunone, and wallichilide, were linked to 414 potential target proteins. From the GSE37924 dataset, 22 candidate target proteins were identified, with folic acid, myricanone, and perlolyrine playing central roles in the network, potentially targeting Adenosylmethionine Decarboxylase 1, Adenosine diphosphate-ribosylation factor 1, Casein Kinase 1 Gamma 2, among others, to mitigate aCVS. Conclusions: L. wallichii and its key components demonstrate potential therapeutic effects in treating aCVS. These findings provide scientific support for the potential therapeutic application of L. wallichii in aCVS treatment, demonstrating the direct value of TCM in modern medical applications.